Comparison of light-transmittance in dental tissues and dental composite restorations using incremental layering build-up with varying enamel resin layer thickness - Rodrigo Rocha Maia; Dayane Oliveira; Tracy D'Antonio; Fang Qian; Frederick Skiff (Restorative Dentistry & Endodontics, 2018)
ObjectivesTo evaluate and compare light-transmittance in dental tissues and dental composite restorations using the incremental double-layer technique with varying layer thickness.Materials and MethodsB1-colored natural teeth slabs were compared to dental restoration build-ups with A2D and B1E-colored nanofilled, supra-nanofilled, microfilled, and microhybrid composites. The enamel layer varied from 0.3, 0.5, or 1.2 mm thick, and the dentin layer was varied to provide a standardized 3.7 mm overall sample thickness (n = 10). All increments were light-cured to 16 J/cm2 with a multi-wave LED (Valo, Ultradent). Using a spectrophotometer, the samples were irradiated by an RGB laser beam. A voltmeter recorded the light output signal to calculate the light-transmittance through the specimens. The data were analyzed using 1-way analysis of variance followed by the post hoc Tukey's test (p = 0.05).ResultsMean light-transmittance observed at thicker final layers of enamel were significantly lower than those observed at thinner final layers. Within 1.2 mm final enamel resin layer (FERL) thickness, all composites were similar to the dental tissues, with exception of the nanofilled composite. However, within 0.5 mm FERL thickness, only the supra-nanofilled composite showed no difference from the dental tissues. Within 0.3 mm FERL thickness, none of the composites were similar to the dental tissues.ConclusionsThe supra-nanofilled composite had the most similar light-transmittance pattern when compared to the natural teeth. However, for other composites, thicker FERL have a greater chance to match the light-transmittance of natural dental tissues.